2012
DOI: 10.1155/2012/862905
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Mortality Rates for Nonvariceal Upper Gastrointestinal Bleeding Differ around the World? A Systematic Review of Cohort Studies

Abstract: Wide differences in reported NVUGIB mortality rates are attributable to differences in adopted methodologies and populations studied. More uniform standards in reporting are needed; only then can true observed variations enable a better understanding of causes of death and pave the way to improved patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
2
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 69 publications
(82 reference statements)
1
20
2
3
Order By: Relevance
“…This was to catch the patients missed to active inclusion and to make sure that the data were as reliable as possible in regard to true incidence rate and mortality. Most studies use database reviews or retrospective cohort designs based on ICD10 codes to execute epidemiological studies [19,[22][23][24][25]. This might increase the risk of misclassification of diagnosis for peptic ulcer bleeding and missing data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was to catch the patients missed to active inclusion and to make sure that the data were as reliable as possible in regard to true incidence rate and mortality. Most studies use database reviews or retrospective cohort designs based on ICD10 codes to execute epidemiological studies [19,[22][23][24][25]. This might increase the risk of misclassification of diagnosis for peptic ulcer bleeding and missing data.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, bleeding from a peptic ulcer is a serious complication, and a mortality rate of up to 10% has previously been reported, despite advances in medical and endoscopic treatment [1,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, patients with peptic ulcer also accounted for a higher proportion. Jairath [ 32 ] reported that the greater difference in the mortality rates of NVUGIB reported worldwide was mainly due to the different research methods and populations in the studies. Multivariate studies found that age ≥80 years, admission to the emergency ward, systolic blood pressure of 50 mmHg, the presence of 2 or more comorbidities, and re-bleeding led to a significant increase in the mortality risk, while emergency endoscopy can reduce the rate of mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The low mortality rate in our cohort is within the range of mortality rates in elderly patients with nonvariceal upper GIB reported in prior studies [ 1 3 , 7 ]. Prior studies on nonvariceal upper GIB in the general population had wide variation in mortality which is believed to be related to the definition of upper GIB and the populations studied [ 16 ]. We chose to define UGIB based on endoscopic findings rather than using presenting symptoms if other than hematemesis.…”
Section: Discussionmentioning
confidence: 99%